Preparation method of indium lithium halide nanocrystalline and all-solid-state battery

Preparation of indium halide lithium nanocrystals by solvent exchange method solves the problems of complex preparation methods and difficult batch preparation in the prior art, and achieves uniformity and efficient battery performance of nanocrystals.

CN119637932APending Publication Date: 2025-03-18CHINA AUTOMOTIVE INNOVATION CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411894658.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The method for preparing lithium indium halide nanocrystals in the prior art has problems such as expensive equipment, complex process, difficult to batch preparation, and difficult to regulate nanocrystal particle size and distribution.

Method used

By using the solvent exchange method, the halide salt of lithium and the halide salt of indium are dissolved in the first solvent, and the crude crystal product is precipitated based on the solvent exchange method, and the indium halide lithium nanocrystals are obtained by mixing with the second solvent.

Benefits of technology

It realizes nanocrystal preparation with simple process, low cost, strong batch preparation ability and good reproducibility. The nanocrystals have small particle size and uniform distribution, which improves the ionic conductivity of the material and the utilization rate of the positive electrode active material, and enhances the rate performance of all solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201395600000212
    Figure BDA0005201395600000212
  • Figure BDA0005201395600000221
    Figure BDA0005201395600000221
  • Figure BDA0005201395600000231
    Figure BDA0005201395600000231
Patent Text Reader

Abstract

The invention relates to the technical field of electrolyte materials, in particular to a preparation method of lithium indium halide nanocrystals and a solid-state battery, the method comprises the following steps: dissolving halide salt of lithium and halide salt of indium in a first solvent to obtain a mixed solution, the first solvent is a good solvent of the lithium indium halide nanocrystals, and the second solvent is a good solvent of the lithium indium halide nanocrystals; the second solvent comprises a poor solvent which can be mutually soluble with the first solvent and is a lithium indium halide nanocrystal, mixing the mixed solution with the second solvent, separating out a crystal crude product based on a solvent exchange method, and cleaning and drying the crystal crude product to obtain the lithium indium halide nanocrystal. The preparation method adopts a solvent exchange method to prepare the lithium indium halide nanocrystal, the process and operation are simple, batch preparation can be realized, the reproducibility is good, the obtained lithium indium halide nanocrystal is relatively small in particle size, uniform in particle size distribution and narrow in distribution peak, the ionic conductivity and yield of the material are improved, the utilization rate of the positive electrode active material is also improved, and the application prospect is wide. And the rate capability of the all-solid-state battery is further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrolyte materials, and in particular to a method for preparing lithium indium halide nanocrystals and an all-solid-state battery. Background Art

[0002] Compared with traditional liquid lithium batteries, solid-state lithium-ion batteries have the advantages of high energy density, small size, high safety, and flexible deformability, so they have attracted much attention. Solid electrolytes are the core components of solid-state batteries. They replace the diaphragms and electrolytes in liquid lithium-ion batteries and have the function of isolating the positive and negative electrodes while transmitting lithium ions. The commonly used solid electrolytes are halide electrolytes, which have good compatibility with positive electrode materials, thus providing all-solid-state batteries with good capacity and high initial coulombic efficiency.

[0003] However, in the case of high surface capacity and high positive electrode ratio, micron-sized halide solid electrolyte particles will limit the utilization rate of positive electrode active materials, thereby leading to poor transport kinetics in the positive electrode composite material in the all-solid-state battery, affecting its electrochemical performance at high current density. In order to solve the above problems, the prior art proposes to use halide solid electrolyte particles with smaller particle size, which can provide a more continuous, uniform and finely dispersed ion conductive network in the positive electrode composite material, greatly improving the transport kinetics in the positive electrode composite material. Inspired by the above-mentioned prior art, the prior art also uses freeze-drying technology to synthesize 80% of indium halide lithium nanocrystals with a particle size of less than 200nm, 15% of less than 400nm, and 3.85% of less than 600nm as solid electrolytes, further improving the charge transfer capacity of the positive electrode composite material.

[0004] However, the existing methods for preparing lithium indium halide nanocrystals generally use freeze-drying, spray drying and other methods. Although they can synthesize lithium indium halide nanocrystals with smaller particle sizes, the above methods have the problems of expensive equipment and complex processes, difficulty in batch preparation, and difficulty in regulating the particle size and distribution of lithium indium halide nanocrystals. Summary of the invention

[0005] In view of the above problems in the prior art, the present application provides a method for preparing lithium indium halide nanocrystals and a solid-state battery. The specific technical solution is as follows:

[0006] In one aspect, the present application provides a method for preparing lithium indium halide nanocrystals, the method comprising:

[0007] S1: dissolving a lithium halide salt and an indium halide salt in a first solvent to obtain a mixed solution, wherein the first solvent is a good solvent for the lithium indium halide nanocrystals;

[0008] S2: providing a second solvent, wherein the second solvent is miscible with the first solvent and is a poor solvent for the lithium indium halide nanocrystals;

[0009] S3: mixing the mixed solution with the second solvent to precipitate a crude crystalline product based on a solvent exchange method;

[0010] S4: washing and drying the crude crystal product to obtain lithium indium halide nanocrystals.

[0011] In a possible implementation manner, the method satisfies at least one of the following characteristics:

[0012] The concentration of the lithium halide salt in the mixed solution is 0.3 to 9 M;

[0013] The concentration of the indium halide salt in the mixed solution is 0.1 to 0.3 M;

[0014] The first solvent includes at least one of water, an alcohol solvent, a cyanide-containing solvent and an ether solvent;

[0015] The poor solvent is a carboxylic acid ester solvent.

[0016] In a possible implementation manner, the second solvent further includes a surfactant, and the surfactant satisfies at least one of the following characteristics:

[0017] The hydrophile-lipophile balance value of the surfactant is 0 to 16;

[0018] The mass proportion of the surfactant in the second solvent is 0.01 to 5 wt %.

[0019] In a possible implementation manner, providing the second solvent includes: mixing the surfactant with the poor solvent to obtain the second solvent.

[0020] In a possible implementation manner, mixing the mixed liquid with the second solvent includes: adding the mixed liquid into the second solvent which is continuously stirred at a certain flow rate and mixing until the first solvent and the poor solvent reach a preset volume ratio.

[0021] In a possible implementation manner, the preset volume ratio is determined based on the mutual solubility of the first solvent and the poor solvent.

[0022] In a possible implementation manner, the method satisfies at least one of the following characteristics:

[0023] The flow rate of adding the second solvent to the mixed solution is 1 to 200 mL / min;

[0024] The stirring speed of the second solvent is 50 to 500 rpm / min;

[0025] The preset volume ratio between the first solvent and the poor solvent is 1:(3.3-50).

[0026] In a possible implementation manner, the method satisfies at least one of the following characteristics:

[0027] The crude crystal product is washed 2 to 5 times;

[0028] The drying process in step S4 includes: performing step-by-step heat treatment on the cleaned crude crystal product to obtain lithium indium halide nanocrystals.

[0029] In a possible implementation manner, the step-by-step heat treatment includes a first heat treatment and a second heat treatment, wherein the heat treatment temperature during the first heat treatment is 100-250°C and the time is 3-5 hours, and the heat treatment temperature during the second heat treatment is 350-450°C and the time is 1-5 hours.

[0030] On the other hand, the present application provides an all-solid-state battery, comprising a positive electrode layer, a negative electrode layer and an isolation layer, wherein at least one of the positive electrode layer and the isolation layer comprises lithium indium halide nanocrystals prepared by the method described in the above embodiment.

[0031] Based on the above technical solution, this application has the following beneficial effects:

[0032] The preparation method of lithium indium halide nanocrystals in the present application comprises dissolving a lithium halide salt and an indium halide salt in a first solvent to obtain a mixed solution, wherein the first solvent is a good solvent for lithium indium halide nanocrystals, and the second solvent comprises a poor solvent for lithium indium halide nanocrystals that is miscible with the first solvent, the mixed solution and the second solvent are mixed, a crude crystal product is precipitated based on a solvent exchange method, and the crude crystal product is cleaned and dried to obtain lithium indium halide nanocrystals. The preparation method adopts a solvent exchange method to prepare lithium indium halide nanocrystals, has simple process and operation, low cost, can be prepared in batches with high yield, and good reproducibility. The obtained lithium indium halide nanocrystals have a small particle size, a uniform particle size distribution, and a narrow distribution peak, which not only improves the ionic conductivity of the material, but also improves the utilization rate of the positive electrode active material, thereby enhancing the rate performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the embodiments or prior art descriptions. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1The present invention is a flow chart of the method for preparing lithium indium halide nanocrystals.

[0035] Figure 2 This is the XRD spectrum of the lithium indium halide nanocrystals obtained in Example 1.

[0036] Figure 3 This is the XRD spectrum of Li3InCl6.

[0037] Figure 4 This is the SEM image of the lithium indium halide nanocrystals obtained in Example 1.

[0038] Figure 5 This is the particle size distribution diagram of the lithium indium halide nanocrystals obtained in Example 1.

[0039] Figure 6 The discharge curve diagram of the all-solid-state battery prepared with the lithium indium halide nanocrystals obtained in Example 7 and Comparative Examples 1-13 and the battery test.

[0040] Figure 7 Schematic diagram of the structure of an all-solid-state battery. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0042] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0043] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0044] The following is a method for preparing lithium indium halide nanocrystals provided in an embodiment of the present application, the method comprising:

[0045] S1: dissolving a lithium halide salt and an indium halide salt in a first solvent to obtain a mixed solution, wherein the first solvent is a good solvent for lithium indium halide nanocrystals;

[0046] In some embodiments, the lithium halide salt includes at least one of lithium chloride, lithium bromide, lithium iodide and lithium fluoride. Preferably, the lithium halide salt is lithium chloride.

[0047] In some embodiments, the halide salt of indium includes at least one of indium chloride, indium bromide and indium iodide. Preferably, the halide salt of indium is indium chloride.

[0048] In some embodiments, the first solvent includes at least one of water, alcohol solvents, cyano-containing solvents and ether solvents. The first solvents of the above types have a higher dielectric constant, can more effectively stabilize the charge of the solute, reduce the aggregation between the solute particles, and help maintain the uniformity and stability of the nanocrystals.

[0049] Preferably, the first solvent is a cyanide-containing solvent. Specifically, the cyanide-containing solvent is acetonitrile. Acetonitrile does not contain oxygen-containing groups, and thus is not easy to absorb water to cause the halide salt to hydrolyze, thereby reducing the impurity content of the nanocrystals.

[0050] In some embodiments, the alcohol solvent includes at least one of ethanol, isopropanol, ethylene glycol and diethylene glycol, and the ether solvent is tetrahydrofuran.

[0051] In some embodiments, dissolving a lithium halide salt and an indium halide salt in a first solvent to obtain a mixed solution includes: dissolving a lithium halide salt and an indium halide salt in a certain molar ratio in the first solvent to obtain a mixed solution.

[0052] Specifically, the molar ratio between the lithium halide salt and the indium halide salt is 3:1.

[0053] In some embodiments, the concentration of the lithium halide salt in the mixed solution is 0.3 to 9 M. The upper limit of the concentration may be, but not limited to, 9 M, 8 M, 7 M, etc., and the lower limit of the concentration may be, but not limited to, 0.3 M, 0.4 M, 0.5 M, etc.; it can be understood that the concentration may also be any point value within the above range, which is not enumerated here.

[0054] In some embodiments, the concentration of the halide salt of indium in the mixed solution is 0.1 to 0.3 M. The upper limit of the concentration may be, but not limited to, 0.3 M, 0.29 M, 0.28 M, etc., and the lower limit of the concentration may be, but not limited to, 0.1 M, 0.11 M, 0.12 M, etc.; it is understandable that the concentration may also be any point value within the above range, which is not enumerated here. Exemplarily, when the concentration of the halide salt of lithium in the mixed solution is 3 M, the concentration of the halide salt of indium in the mixed solution is 1 M; when the concentration of the halide salt of lithium in the mixed solution is 0.3 M, the concentration of the halide salt of indium in the mixed solution is 0.1 M.

[0055] By adjusting the initial concentrations of the indium halide salt and the lithium halide salt to control the nucleation density of the nanocrystals, the particle size and yield of the indium halide lithium nanocrystals can be regulated. When the initial concentrations of the two are high, nanocrystals with smaller particle size and higher yield will be produced. When the initial concentrations of the two are low, the particle size of the nanocrystals is larger and the yield is lower. S2: providing a second solvent, the second solvent comprising a poor solvent that is miscible with the first solvent and is a poor solvent for the indium halide lithium nanocrystals;

[0056] In some embodiments, the second solvent includes a surfactant, and the hydrophilic-lipophilic balance value of the surfactant is 0 to 16. The upper limit of the hydrophilic-lipophilic balance value may be, but not limited to, 16, 15, 14, etc., and the lower limit of the hydrophilic-lipophilic balance value may be, but not limited to, 0, 1, 2, etc.; it is understandable that the hydrophilic-lipophilic balance value may also be any point value within the above range, which is not enumerated here. Preferably, the hydrophilic-lipophilic balance value of the surfactant is 3 to 6. Further preferably, the hydrophilic-lipophilic balance value of the surfactant is 6. By limiting the hydrophilic-lipophilic balance value of the surfactant, it can be ensured that it can be effectively adsorbed on the surface of the nanocrystal to form a protective layer, thereby maintaining the stability and dispersibility of the nanocrystals, and also avoiding the problem that the hydrophilic-lipophilic balance value of the surfactant is too high or too low, making it difficult to disperse in a poor solvent.

[0057] In some embodiments, the surfactant includes at least one of glyceryl monostearate, polyglycerol esters and polydimethylsilicone. Preferably, the surfactant is glyceryl monostearate.

[0058] Specifically, the hydrophilic-lipophilic balance value of glyceryl monostearate is 6, the hydrophilic-lipophilic balance value of polyglycerol ester is 3, and the hydrophilic-lipophilic balance value of polydimethylsilicone is 4.

[0059] In some embodiments, the mass proportion of the surfactant in the second solvent is 0.01-5wt%. The upper limit of the mass proportion may be but not limited to 5wt%, 4wt%, 3wt%, etc., and the lower limit of the mass proportion may be but not limited to 0.01wt%, 0.02wt%, 0.03wt%, etc.; it can be understood that the mass proportion can also be any point value within the above range, which is not enumerated here. By limiting the mass proportion, it is to avoid excessive stabilization caused by excessive surfactant adsorption on the surface of the nanocrystal, resulting in poor application performance of the prepared nanocrystals. In addition, excessive surfactants may introduce additional impurities, thereby affecting the purity of the final nanocrystals. Preferably, the mass proportion of the surfactant in the second solvent is 0.1-0.5wt%. Further preferably, the mass proportion of the surfactant in the second solvent is 0.1wt%.

[0060] In some embodiments, providing the second solvent includes: mixing a surfactant with a poor solvent to obtain the second solvent. By adding the surfactant to the second solvent, the surfactant can be effectively adsorbed on the surface of the nanocrystals, thereby preventing the nanocrystals from agglomerating.

[0061] In some embodiments, the poor solvent is a carboxylate solvent. The carboxylate solvent has a low solubility for the formed lithium indium halide nanocrystals and has good compatibility with the first solvent, thereby greatly promoting the precipitation and aggregation of the lithium indium halide nanocrystals.

[0062] Specifically, the carboxylate solvent includes at least one of ethyl acetate, ethyl formate, propyl propionate, methyl formate and propyl acetate. Preferably, the carboxylate solvent is ethyl acetate. The above carboxylate solvent has a low dielectric constant and is difficult to dissolve lithium indium halide nanocrystals, thereby promoting the precipitation of lithium indium halide nanocrystals. S3: mixing the mixed solution with the second solvent, and precipitating a crude crystal product based on a solvent exchange method;

[0063] In some embodiments, the mixed liquid is mixed with the second solvent, and a crude crystal product is precipitated based on a solvent exchange method, including: adding the mixed liquid to the continuously stirred second solvent at a certain flow rate and mixing until the first solvent and the poor solvent reach a preset volume ratio. By limiting the flow rate of the mixed liquid, it is possible to ensure that the poor solvent can be quickly and continuously exchanged with the first solvent during the mixing process, which is conducive to the formation of uniform nanocrystals with a narrow distribution particle size. The second solvent is continuously stirred during the addition process, so that the second solvent can be fully in contact with the surface of the nanocrystals, which promotes the solvent exchange rate, avoids the uneven reaction caused by too slow stirring speed, and avoids the excessive shear force that may be introduced due to too fast stirring speed, thereby causing the agglomeration of nanocrystals.

[0064] In some embodiments, the preset volume ratio is determined based on the mutual solubility of the first solvent and the poor solvent. When the mutual solubility of the first solvent and the poor solvent is too high, nanocrystals may not be effectively formed, and the mutual solubility of the first solvent and the poor solvent is too low, then the poor solvent may not be fully mixed with the first solvent, thereby affecting the formation and dispersion of nanocrystals. Therefore, by optimizing the preset volume ratio of the first solvent and the poor solvent, it is mainly to control the supersaturation and nucleation rate of the solute in the first solvent, thereby being able to affect the size, shape and dispersibility of the nanocrystals.

[0065] In some embodiments, the preset volume ratio between the first solvent and the poor solvent is 1:(3.3-50). When the ratio of the first solvent is too high, it may cause excessive growth of nanocrystals and lose the ideal morphology and size control, while when the ratio of the poor solvent is too high, it may cause the precursor or early formed nanocrystals in the first solvent to fail to precipitate effectively, thereby affecting the yield and purity of the nanocrystals. Therefore, the present application limits the preset volume ratio between the first solvent and the poor solvent to 1:(3.3-50).

[0066] Exemplarily, the first solvent is water, the poor solvent is ethyl acetate, and the preset volume ratio between the first solvent and the poor solvent is 1:(3.3-25); the first solvent is water, the poor solvent is ethyl formate, and the preset volume ratio between the first solvent and the poor solvent is 1:9; the first solvent is water, the poor solvent is propyl propionate, and the preset volume ratio between the first solvent and the poor solvent is 1:40; the first solvent is water, the poor solvent is methyl formate, and the preset volume ratio between the first solvent and the poor solvent is 1:3.3; the first solvent is water, the poor solvent is propyl acetate, and the preset volume ratio between the first solvent and the poor solvent is 1:50.

[0067] In some embodiments, the flow rate of the mixed solution adding the second solvent is 1 to 200 mL / min. The upper limit of the flow rate may be, but not limited to, 200 mL / min, 199 mL / min, 198 mL / min, etc., and the lower limit of the flow rate may be, but not limited to, 1 mL / min, 2 mL / min, 3 mL / min, etc.; it is understandable that the flow rate may also be any point value within the above range, which is not enumerated here. The flow rate mainly affects the solvent exchange rate during the mixing process. The appropriate solvent exchange rate can control the quality and size of the nanocrystals. This application limits the flow rate, on the one hand, to avoid the flow rate being too fast, which will cause the poor solvent to be unable to effectively replace the good solvent on the surface of the nanocrystal, thereby causing the nanocrystals to agglomerate and have a larger particle size, and on the other hand, to avoid the problem of low production efficiency due to too slow a flow rate. Preferably, the flow rate of the mixed solution adding the second solvent is 1 to 10 mL / min. Further preferably, the flow rate of the mixed solution adding the second solvent is 3 to 10 mL / min. Further, the flow rate of the mixed solution adding the second solvent is 10 mL / min.

[0068] In some embodiments, the stirring speed of the second solvent is 50 to 500 rpm / min. The upper limit of the stirring speed may be, but is not limited to, 500 rpm / min, 499 rpm / min, 498 rpm / min, etc., and the lower limit of the stirring speed may be, but is not limited to, 50 rpm / min, 51 rpm / min, 52 rpm / min, etc.; it is understandable that the stirring speed may also be any point value within the above range, which is not enumerated here. The stirring speed mainly affects the mixing rate between the first solvent and the poor solvent, the nucleation and growth environment of the nanocrystals. By limiting the above stirring speed, the uniform mixing of the first solvent and the second solvent can be promoted, thereby promoting the formation of nanocrystals, and nanocrystals with narrow particle size distribution and small particle size can be obtained. Preferably, the stirring speed of the second solvent is 200 to 300 rpm / min. Further preferably, the stirring speed of the second solvent is 300 rpm / min.

[0069] In some embodiments, after the mixed solution is mixed with the second solvent and a crude crystalline product is precipitated based on a solvent exchange method, the method further comprises: separating the suspension obtained after the mixed solution and the second solvent are mixed to obtain a crude crystalline product.

[0070] Specifically, the separation process includes: vacuum filtering the suspension obtained by mixing the mixed solution with the second solvent. S4: washing and drying the crude crystal product to obtain lithium indium halide nanocrystals.

[0071] In some embodiments, the crude crystal product is washed, including: washing the crude crystal product with a poor solvent to obtain a washed crude crystal product. When the crude crystal product is washed, in order to fully remove the residual organic solvent on the crude crystal product, it is prevented that the carbonization phenomenon on the surface of the nanocrystals occurs during the subsequent drying process, thereby affecting the conductivity of the nanocrystals. Specifically, the crude crystal product is washed 2 to 5 times. It can be understood that the number of washings can also be any point value within the above range, which is not enumerated here. Preferably, the crude crystal product is washed 2 to 3 times. Further preferably, the crude crystal product is washed 3 times.

[0072] In some embodiments, the drying process in step S4 includes: performing a step-by-step heat treatment on the cleaned crude crystal product to obtain lithium indium halide nanocrystals. Drying the crude crystal product by step-by-step heat treatment can not only fully remove the organic solvent remaining on the surface of the nanocrystals, but also further induce the further crystallization of the nanocrystals. In some embodiments, the step-by-step heat treatment includes a first heat treatment and a second heat treatment, the heat treatment temperature in the first heat treatment process is 100 to 250°C, the time is 3 to 5 hours, and the heat treatment temperature in the second heat treatment process is 350 to 450°C, and the time is 1 to 5 hours. It can be understood that the heat treatment temperature and time in the first heat treatment process and the heat treatment temperature and time in the second heat treatment process can also be any point value within the above range, which is not enumerated here. By limiting the heat treatment temperature and time in the first heat treatment process, the residual solvent molecules on the surface of the nanocrystal can be removed, and the chelation reaction on the surface of the nanocrystal during the second heat treatment can be avoided, thereby reducing its conductivity. By limiting the heat treatment temperature and time in the second heat treatment process, the further crystallization or phase stability of the nanocrystal can be further induced, and the internal structure of the nanocrystal can be changed due to excessively high temperature, thereby affecting its comprehensive performance. Preferably, the heat treatment temperature in the first heat treatment process is 100°C and the time is 3 to 4 hours, and the heat treatment temperature in the second heat treatment process is 350 to 400°C and the time is 3 to 5 hours. Further preferably, the heat treatment temperature in the first heat treatment process is 100°C and the time is 3 hours, and the heat treatment temperature in the second heat treatment process is 400°C and the time is 3 hours.

[0073] In some embodiments, the drying process in step S4 is performed under a vacuum environment.

[0074] The present application adopts a solvent exchange method to prepare lithium indium halide nanocrystals. The process and operation are simple, and batch preparation is possible with good reproducibility. The obtained lithium indium halide nanocrystals have a small particle size, uniform particle size distribution and narrow distribution peak, which not only improves the ionic conductivity of the material and has a high yield, but also improves the utilization rate of the positive electrode active material, thereby enhancing the rate performance of the all-solid-state battery. In addition, since the obtained lithium indium halide nanocrystals have a small particle size, they have a higher specific surface area, and only a small amount of lithium indium halide nanocrystals are needed to cover the surface of the positive electrode active material, and can effectively balance the release of elastic properties during the reaction of the first solid electrolyte with other substances, effectively avoiding the breakage and cracking of the solid electrolyte. The use of a smaller-sized Li3InCl6 nanocrystal solid electrolyte can significantly reduce the roughness of the interface between the first solid electrolyte layer and the positive electrode layer, effectively reducing the contact gap between the interfaces or the pores caused by the uneven distribution of the positive electrode. A more uniform interface brings a more uniform current distribution, thereby greatly reducing the damage caused by the interfacial electrochemical-mechanical stress to the battery cycle performance. This embodiment also provides an all-solid-state battery, as shown in the attached Figure 6As shown, it includes a positive electrode layer, a negative electrode layer and a separator, and at least one of the positive electrode layer and the separator includes lithium indium halide nanocrystals prepared by the method described in the above embodiments. At least one of the positive electrode layer and the separator includes lithium indium halide nanocrystals, which can significantly reduce the roughness of the interface between the first solid electrolyte layer and the positive electrode layer, effectively reduce the contact gap between the interfaces or the pores caused by the uneven distribution of the positive electrode, and a more uniform interface brings a more uniform current distribution, thereby greatly reducing the damage caused by the interfacial electrochemical-mechanical stress to the battery cycle performance, and significantly improving the battery rate performance. Specifically, the separator includes a positive electrode side electrolyte layer and a negative electrode side electrolyte layer, and at least one of the positive electrode layer and the positive electrode side electrolyte layer includes lithium indium halide nanocrystals prepared by the method described in the above embodiments.

[0075] In some embodiments, both the positive electrode layer and the isolation layer include lithium indium halide nanocrystals prepared by the method described in the above embodiments.

[0076] Specifically, the positive electrode layer includes a positive electrode active material, a first solid electrolyte, and lithium indium halide nanocrystals.

[0077] In some embodiments, the positive electrode active material may be an oxide active material or a sulfide active material.

[0078] Specifically, the oxide active material may be LiCoO2, LiMnO2, LiNiO2, LiVO2, Li 1+x Ni 1 / 3 Co 1 / 3Mn 1 / 3 O2 and other rock salt layer type active materials, such as LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4, etc., spinel-type active materials such as LiNiVO4, LiCoVO4, etc., olivine-type active materials such as LiFePO4, LiMnPO4, LiCoPO4, LiNiPO4, etc., silicon-containing active materials such as Li2FeSiO4, Li2MnSiO4, etc., such as LiNi 0.8 Co (0.2-x) Al x O2 (0<x<0.2) wherein a portion of the transition metal is replaced by a different metal, such as Li 1+x Mn 2-x- y M y O4 (M is at least one of Al, Mg, Co, Fe, Ni and Zn, 0<x+y<2) wherein a part of the transition metal is replaced by a different metal or a spinel type active material such as Li4Ti5O 12 Lithium titanate, etc.

[0079] Specifically, the sulfide active material may be copper sulfide, iron sulfide, cobalt sulfide, nickel sulfide, or the like.

[0080] In some embodiments, the negative electrode layer includes lithium indium halide nanocrystals prepared by the method described in the above embodiments, a first solid electrolyte, and a negative electrode active material.

[0081] Specifically, the negative electrode active material includes at least one of a metal material, a carbon material, an oxide, a nitride, a tin compound and a silicon compound. Specifically, the metal material can be a simple metal material, such as lithium metal, or an alloy, such as a lithium alloy; the carbon material can be natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon, etc. From the viewpoint of capacity density, at least one selected from silicon (Si), tin (Sn), a silicon compound and a tin compound can also be appropriately used.

[0082] In some embodiments, the isolation layer includes a first solid electrolyte and lithium indium halide nanocrystals prepared by the method described in the above embodiments.

[0083] Specifically, the first solid electrolyte includes an oxide solid electrolyte or a sulfide solid electrolyte. Here, it is preferred to use a sulfide solid electrolyte with high lithium ion conductivity. The sulfide solid electrolyte is not particularly limited and may be Li3YCl6, Li3InCl6, Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (where m and n are positive numbers, and Z is one of Ge, Zn and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In), Li 10 GeP2S 12 wait.

[0084] The following is an introduction to the specific embodiments of the present application in conjunction with the above-mentioned method for preparing halide indium lithium nanocrystals. The following embodiments describe the technical solution of the present application in more detail, and these embodiments are only used for illustrative purposes, because various modifications and changes within the scope of the disclosure of the present application are obvious to those skilled in the art. The reagents used in the embodiments can be obtained commercially or synthesized according to conventional methods, and can be used directly without further treatment, and the instruments and devices used in the embodiments can be obtained commercially.

[0085] Example 1

[0086] This embodiment provides a method for preparing halide indium lithium nanocrystals, the method comprising:

[0087] S1: LiCl and InCl3 are weighed at a molar ratio of 3:1, and the weighed LiCl and InCl3 are dissolved in 1 L of deionized water at a concentration of 9M:3M to obtain a mixed solution;

[0088] S2: dissolving 0.1 wt % of glyceryl monostearate (HLB=6) in 11 L of ethyl acetate to obtain a second solvent;

[0089] S3: adding the mixed solution to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and ethyl acetate is 1:11 to obtain a suspension, and vacuum filtering the suspension to obtain a crude crystalline product;

[0090] S4: The crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0091] Example 2

[0092] This embodiment provides a method for preparing lithium indium halide nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is as follows: S1: LiCl and InCl3 are weighed at a molar ratio of 3:1, and the weighed LiCl and InCl3 are dissolved in 1L of deionized water at a concentration of 3M:1M to obtain a mixed solution.

[0093] Example 3

[0094] This embodiment provides a method for preparing lithium indium halide nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is as follows: S1: LiCl and InCl3 are weighed at a molar ratio of 3:1, and the weighed LiCl and InCl3 are dissolved in 1L of deionized water at a concentration of 0.3M:0.1M to obtain a mixed solution.

[0095] Example 4

[0096] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is ethanol.

[0097] Example 5

[0098] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is isopropanol.

[0099] Example 6

[0100] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is tetrahydrofuran.

[0101] Example 7

[0102] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is acetonitrile.

[0103] Example 8

[0104] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is ethylene glycol.

[0105] Example 9

[0106] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is diethylene glycol.

[0107] Example 10

[0108] This embodiment provides a method for preparing halide indium lithium nanocrystals. The same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the surfactant in step S2 is polyglycerol ester (HLB=3).

[0109] Embodiment 11

[0110] This embodiment provides a method for preparing lithium indium halide nanocrystals. The same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the surfactant in step S2 is polydimethylsilicone oil (HLB=4).

[0111] Example 12

[0112] This embodiment provides a method for preparing halide indium lithium nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is as follows: S2: 0.01 wt % of glyceryl monostearate (HLB=6) is dissolved in 11 L of ethyl acetate to obtain a second solvent.

[0113] Embodiment 13

[0114] This embodiment provides a method for preparing lithium indium halide nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is as follows: S2: 5 wt % of glyceryl monostearate (HLB=6) is dissolved in 11 L of ethyl acetate to obtain a second solvent.

[0115] Embodiment 14

[0116] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of glyceryl monostearate (HLB=6) in 9 L of ethyl formate to obtain a second solvent;

[0117] S3: adding the mixed solution to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and ethyl formate is 1:9 to obtain a suspension, and vacuum filtering the suspension to obtain a crude crystalline product;

[0118] S4: The crude crystal product is washed three times with ethyl formate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0119] Embodiment 15

[0120] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of glyceryl monostearate (HLB=6) in 40 L of propyl propionate to obtain a second solvent;

[0121] S3: adding the mixed solution to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and propyl propionate is 1:40 to obtain a suspension, and vacuum filtering the suspension to obtain a crude crystalline product;

[0122] S4: The crude crystal product is washed three times with propyl propionate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0123] Example 16

[0124] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of glyceryl monostearate (HLB=6) in 3.3 L of methyl formate to obtain a second solvent;

[0125] S3: adding the mixed solution to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and methyl formate is 1:3.3, thereby obtaining a suspension, and vacuum filtering the suspension to obtain a crude crystalline product;

[0126] S4: The crude crystal product is washed three times with methyl formate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0127] Embodiment 17

[0128] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of glyceryl monostearate (HLB=6) in 50 L of propyl acetate to obtain a second solvent;

[0129] S3: adding the mixed solution to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and propyl acetate is 1:50 to obtain a suspension, and vacuum filtering the suspension to obtain a crude crystalline product;

[0130] S4: The crude crystal product is washed three times with propyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0131] Embodiment 18

[0132] This embodiment provides a method for preparing halide indium lithium nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is that the flow rate of adding the second solvent to the mixed solution in step S3 is 1 mL / min.

[0133] Embodiment 19

[0134] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Example 1 are not repeated here. The difference from Example 1 is that the flow rate of adding the second solvent to the mixed solution in step S3 is 200 mL / min.

[0135] Embodiment 20

[0136] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference from Embodiment 1 is that the stirring speed of the second solvent in step S3 is 50 rpm / min.

[0137] Embodiment 21

[0138] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the stirring speed of the second solvent in step S3 is 500 rpm / min.

[0139] Embodiment 22

[0140] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of monostearate glycerol (HLB=6) in 25 L of ethyl acetate to obtain a second solvent;

[0141] S3: The mixed solution is added to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and ethyl acetate is 1:25, to obtain a suspension, and the suspension is vacuum filtered to obtain a crude crystalline product.

[0142] Embodiment 23

[0143] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of monostearate glycerol (HLB=6) in 15 L of ethyl acetate to obtain a second solvent;

[0144] S3: The mixed solution is added to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and ethyl acetate is 1:15, to obtain a suspension, and the suspension is vacuum filtered to obtain a crude crystalline product.

[0145] Embodiment 24

[0146] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of monostearate glycerol (HLB=6) in 3.3 L of ethyl acetate to obtain a second solvent;

[0147] S3: The mixed solution is added to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and ethyl acetate is 1:3.3, to obtain a suspension, and the suspension is vacuum filtered to obtain a crude crystalline product.

[0148] Embodiment 25

[0149] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed twice with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours, respectively, to obtain Li3InCl6 nanocrystals.

[0150] Embodiment 26

[0151] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed 5 times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours, respectively, to obtain Li3InCl6 nanocrystals.

[0152] Embodiment 27

[0153] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 250°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0154] Embodiment 28

[0155] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 5 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0156] Embodiment 29

[0157] The present embodiment provides a method for preparing lithium indium halide nanocrystals, and the similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3h and at a heat treatment temperature of 350°C for 1h to obtain Li3InCl6 nanocrystals.

[0158] Embodiment 30

[0159] The present embodiment provides a method for preparing lithium indium halide nanocrystals, and the similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 450°C for 5 hours to obtain Li3InCl6 nanocrystals.

[0160] Comparative Example 1

[0161] This comparative example provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S1: LiCl and InCl3 are weighed at a molar ratio of 3:1, and the weighed LiCl and InCl3 are dissolved in 1L of deionized water at a concentration of 0.03M:0.01M to obtain a mixed solution.

[0162] Comparative Example 2

[0163] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the first solvent in step S1 is triethylene glycol.

[0164] Comparative Example 3

[0165] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in Example 1 are not repeated here. The difference between this method and Example 1 is that the surfactant glyceryl monostearate is not added.

[0166] Comparative Example 4

[0167] This embodiment provides a method for preparing lithium indium halide nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is as follows: S2: dissolving 10 wt % of glyceryl monostearate (HLB=6) in 11 L of ethyl acetate to obtain a second solvent.

[0168] Comparative Example 5

[0169] This embodiment provides a method for preparing lithium indium halide nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is that: S2: dissolving 0.1 wt % of glyceryl monostearate (HLB=6) in 11 L of isooctane to obtain a second solvent;

[0170] S3: adding the mixed solution to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and isooctane is 1:11 to obtain a suspension, and vacuum filtering the suspension to obtain a crude crystalline product;

[0171] S4: The crude crystalline product is washed three times with isooctane to obtain a washed crude crystalline product, and the washed crude crystalline product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0172] Comparative Example 6

[0173] This embodiment provides a method for preparing halide indium lithium nanocrystals. The same points as those in Example 1 are not repeated here. The difference from Example 1 is that the flow rate of adding the second solvent to the mixed solution in step S3 is 300 mL / min.

[0174] Comparative Example 7

[0175] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in Embodiment 1 are not repeated here. The difference between this embodiment and Embodiment 1 is that the stirring speed of the second solvent in step S3 is 0 rpm / min.

[0176] Comparative Example 8

[0177] This embodiment provides a method for preparing halide indium lithium nanocrystals, and the same points as those in embodiment 1 are not repeated here, and the difference from embodiment 1 is as follows: S2: dissolving 0.1 wt % of monostearate glycerol (HLB=6) in 1 L of ethyl acetate to obtain a second solvent;

[0178] S3: The mixed solution is added to the second solvent with a stirring speed of 300 rpm / min at a flow rate of 10 mL / min until the preset volume ratio between deionized water and ethyl acetate is 1:1 to obtain a suspension, and the suspension is vacuum filtered to obtain a crude crystalline product.

[0179] Comparative Example 9

[0180] This embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is that: S4: the crude crystal product is treated at a heat treatment temperature of 100°C for 3 hours and at a heat treatment temperature of 400°C for 3 hours to obtain Li3InCl6 nanocrystals.

[0181] Comparative Example 10

[0182] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 0.1h and at a heat treatment temperature of 400°C for 3h to obtain Li3InCl6 nanocrystals.

[0183] Comparative Example 11

[0184] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 40°C for 3h and at a heat treatment temperature of 400°C for 3h to obtain Li3InCl6 nanocrystals.

[0185] Comparative Example 12

[0186] The present embodiment provides a method for preparing lithium indium halide nanocrystals, and the similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3h and at a heat treatment temperature of 400°C for 0.1h to obtain Li3InCl6 nanocrystals.

[0187] Comparative Example 13

[0188] The present embodiment provides a method for preparing lithium indium halide nanocrystals. The similarities with Example 1 are not repeated here. The difference from Example 1 is as follows: S4: the crude crystal product is washed three times with ethyl acetate to obtain a washed crude crystal product, and the washed crude crystal product is treated at a heat treatment temperature of 100°C for 3h and at a heat treatment temperature of 300°C for 3h, respectively, to obtain Li3InCl6 nanocrystals.

[0189] The above examples and comparative examples adopt the following testing methods:

[0190] 1. XRD test: X-ray diffraction data of the halide indium lithium nanocrystals obtained in Example 1 were measured using an X-ray diffractometer. The setting conditions were: acceleration voltage 40KV, Cu target, incident light wavelength between 0.1 and 1.54nm. The test results are as follows: Figure 2 As shown in the figure, it can be seen that the XRD peak position and peak intensity are completely consistent with the Li3InCl6 standard card (see attached Figure 3 ), indicating that the synthesized material is a pure phase substance without impurities.

[0191] 2. Ionic conductivity test: In an argon atmosphere, the nanocrystalline powder prepared by the embodiment and the comparative example is filled inside the pressurized mold. Inside the pressurized mold, a pressure of 500MPa is applied to the powder of the solid electrolyte material using upper and lower punches. While keeping the pressure unchanged, the upper and lower parts of the punches are respectively connected to a constant potential instrument equipped with a frequency response analyzer, and the ionic conductivity of the solid electrolyte material is measured by the electrochemical impedance method. The real value of the impedance at the measuring point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte material to ionic conduction.

[0192] 3. Particle size test: The nanocrystals prepared in the examples and comparative examples were dissolved in ethyl acetate to obtain a dispersion with a concentration of 10 mg / mL. The particle size was measured using a BT-200 laser particle size analyzer made by Micro Dandong Biotech. The test results are shown in the attached figure. Figure 5 shown.

[0193] 4. SEM test: The morphology of the halide lithium indium nanocrystals obtained in Example 1 was observed by scanning electron microscope (model Sigma300-Gemini1). The test results are shown in the attached figure. Figure 4 As shown, the particle size of the Li3InCl6 nanocrystals prepared in Example 1 is small and evenly distributed.

[0194] 4. Rate performance test of all-solid-state batteries.

[0195] (1) Assembly of all-solid-state batteries:

[0196] S11: In an argon atmosphere, Li3InCl6 nanocrystals and positive electrode active material LiN are mixed in a mass ratio of 10:90. i0.8 Co 0.1 Mn 0.1 O2 is mixed to obtain a positive electrode mixture;

[0197] S12: In an insulating cylinder, Li3InCl6 nanocrystals (60 mg) and Li6PS5Cl solid electrolyte material (24 mg) are stacked in sequence to obtain a first stack, and a pressure of 160 MPa is applied to the first stack to form a separator; a positive electrode mixture (10 mg) is stacked on the separator to obtain a second stack, and a pressure of 360 MPa is applied to the second stack to form a positive electrode layer; a metal lithium foil (thickness of 300 μm) is stacked on the separator to obtain a third stack, and a pressure of 5 MPa is applied to the third stack to form a negative electrode layer;

[0198] S13: A current collector formed of stainless steel is arranged on the positive electrode layer and the negative electrode layer, a current collecting lead is installed on the current collector, an insulating hoop is used to isolate the inside of the insulating tube from the external atmosphere, and then the inside of the insulating tube is sealed to obtain an all-solid-state battery.

[0199] (2) The electrochemical performance of the all-solid-state battery was tested using a Shenzhen Xinweier (model CT-4008Tn-5V10mA-164) battery tester. The battery was subjected to a 0.1-1C electrochemical performance test in the voltage range of 2.5-4.2V. A 1C discharge capacity greater than 80% of the 0.1C discharge capacity was considered excellent, a 1C discharge capacity greater than 60% of the 0.1C discharge capacity was considered good, a 1C discharge capacity greater than 40% of the 0.1C discharge capacity was considered medium, and a 1C discharge capacity less than 40% of the 0.1C discharge capacity was considered poor. The test results are shown in the attached Figure 6 And as shown in Table 1.

[0200] 5. Yield calculation: The total mass of the nanocrystals obtained in the embodiment and the comparative example is respectively set as the sample mass m, the volume of the first solvent is V1, and the volume of the poor solvent is V2.

[0201] 6. The following Table 1 statistically records the test data in the embodiments and comparative examples:

[0202] Table 1

[0203]

[0204]

[0205]

[0206] Referring to Table 1 and the accompanying drawings, in combination with Examples 1-3 and Comparative Example 1, it can be seen that, when other conditions remain unchanged, the higher the concentration of lithium chloride and indium chloride in the first solvent, the particle size of the obtained nanocrystals will gradually decrease. This may be because after nucleation, a high concentration of reactants still exists in the first solvent phase, and can continue to react with the crystal nuclei in the poor solvent, resulting in continued growth of the nanocrystals. The particle size of the formed nanocrystals is larger, but the lower concentration of lithium chloride and indium chloride in the first solvent will result in a lower yield.

[0207] Combining Examples 4-9 and Comparative Example 2, it can be seen that suitable first solvents are water, ethanol, tetrahydrofuran and acetonitrile with strong dielectric constants and polarities. The above-mentioned types of first solvents can not only dissolve indium chloride and lithium chloride well, but also be miscible with poor solvents, promote the precipitation of crystals, and improve the ionic conductivity of the nanocrystals and the rate performance of the battery. When the first solvent is triethylene glycol, the rate performance of the obtained battery is poor, which may be due to the high viscosity of triethylene glycol, which will cause the concentration of the solute to change slowly during the solvent exchange process, thereby resulting in a larger nanocrystal particle size and poor battery rate performance. When the first solvent is acetonitrile, the ionic conductivity of the obtained nanocrystals is the highest, which may be due to the fact that acetonitrile does not contain oxygen groups and the obtained nanocrystals have fewer impurities, so the ionic conductivity of the material is higher.

[0208] Combining Examples 10-11 and Comparative Example 3, it can be seen that when other conditions remain unchanged, after adding the surfactant, the particle size of the nanocrystals is small and the particle size distribution is uniform, and the rate performance of the resulting battery is good, mainly because the nanocrystals tend to agglomerate due to their large specific surface area and high surface energy, and the addition of the surfactant can be adsorbed on the surface of the particles to form a protective layer, reducing the interaction force between the particles, thereby effectively preventing agglomeration. Combining Examples 12-13 and Comparative Example 4, it can be seen that when other conditions remain unchanged, a large amount of surfactant is used, which will lead to a decrease in the ionic conductivity of the material and the rate performance of the battery, mainly because an excess of surfactant may be adsorbed on the surface of the nanocrystal to form an overly tight protective layer, which may hinder the interaction between the nanocrystals, and in the subsequent processing process, it will make it difficult to remove the surfactant on the surface of the crystal, thereby reducing the purity of the nanocrystals.

[0209] In combination with Examples 14-17, it can be seen that different types of poor solvents have different addition amounts. The addition amount of the poor solvent is determined based on the mutual solubility of different types of poor solvents and the first solvent. Different types of poor solvents and addition amounts will have a certain effect on the ionic conductivity of the material and the rate performance of the battery, but will not affect the particle size and distribution of the nanocrystals.

[0210] Combining Example 1 and Comparative Example 5, it can be seen that when other conditions remain unchanged and isooctane, which is insoluble in the first solvent, is selected as a poor solvent, the particle size of the nanocrystals increases significantly and the rate performance of the battery is poor, because isooctane cannot occupy the space of water molecules to allow the mixed liquid to precipitate crystal nuclei and grow, and nanocrystals of suitable particle size cannot be obtained, and only large blocks can be obtained.

[0211] Combining Examples 18-19 and Comparative Example 6, it can be seen that, with other conditions remaining unchanged, increasing the flow rate at which the mixed liquid is added to the second solvent will result in larger nanocrystal particle size and poorer rate performance of the battery. This may be because too fast a flow rate affects the solvent exchange rate, which in turn affects the morphology and size of the nanocrystals.

[0212] Combining Examples 20-21 and Comparative Example 7, it can be seen that if other conditions remain unchanged and the second solvent is not stirred during the mixing process, the particle size distribution of the nanocrystals will be uneven and the particle size will be larger, and the rate performance of the battery will also be poor. This is mainly because without stirring, the poor solvent may only be able to form exchange in a local area on the surface of the nanocrystal, resulting in inconsistent shape and size of the nanocrystals.

[0213] From Examples 22-24 and Comparative Example 8, it can be seen that, when other conditions remain unchanged, changing the preset volume ratio of the first solvent and the poor solvent will have a significant effect on the particle size of the nanocrystals and the rate performance of the battery. When the preset volume ratio is 1:1, that is, when the amount of the poor solvent added is too small, it may cause excessive growth of the nanocrystals and an increase in the particle size of the nanocrystals.

[0214] Combining Examples 25-26 and Comparative Example 9, it can be seen that if other conditions remain unchanged and the crude crystal product is not washed, surfactants will remain on the surface of the crystals, causing carbonization during the subsequent heat treatment process, resulting in the surface of the crystals being coated with carbon, which in turn leads to high electronic conductivity of the nanocrystals, affecting the performance and safety of the battery.

[0215] Combining Examples 27-28 and Comparative Examples 10-11, it can be seen that, when other conditions remain unchanged, a shorter time or lower temperature in the first step of heat treatment will result in incomplete removal of the organic solvent remaining on the crystal surface, thereby resulting in poor rate performance of the battery.

[0216] Combining Examples 29-30 and Comparative Examples 12-13, it can be seen that, if other conditions remain unchanged, the time for the second step heat treatment is too short or the temperature is too low, the nanocrystals will not be able to further crystallize and will not be able to further promote the development of the nanocrystals, resulting in a decrease in the conductivity and rate performance of the nanocrystals.

[0217] As shown in Table 1 above, the minimum particle size of the lithium indium halide nanocrystals obtained by the preparation method of lithium indium halide nanocrystals of the present application can reach 7nm, the ion conductivity is as high as 3.72mS / cm, the yield is as high as 87.00%, and the ratio of the discharge capacity of the all-solid-state battery at 1C to the discharge capacity at 0.1C can reach more than 80%, proving that the all-solid-state battery has excellent rate performance.

[0218] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. A method for preparing lithium indium halide nanocrystals, characterized in that: The method comprises: S1: dissolving a lithium halide salt and an indium halide salt in a first solvent to obtain a mixed solution, wherein the first solvent is a good solvent for the lithium indium halide nanocrystals; S2: providing a second solvent, wherein the second solvent is miscible with the first solvent and is a poor solvent for the lithium indium halide nanocrystals; S3: mixing the mixed solution with the second solvent to precipitate a crude crystalline product based on a solvent exchange method; S4: washing and drying the crude crystal product to obtain lithium indium halide nanocrystals.

2. The method according to claim 1, characterized in that The method satisfies at least one of the following characteristics: The concentration of the lithium halide salt in the mixed solution is 0.3 to 9 M; The concentration of the indium halide salt in the mixed solution is 0.1 to 0.3 M; The first solvent includes at least one of water, an alcohol solvent, a cyanide-containing solvent and an ether solvent; The poor solvent is a carboxylic acid ester solvent.

3. The electrolyte according to claim 1, characterized in that The second solvent further comprises a surfactant, and the surfactant satisfies at least one of the following characteristics: The hydrophile-lipophile balance value of the surfactant is 0 to 16; The mass proportion of the surfactant in the second solvent is 0.01 to 5 wt %.

4. The method according to claim 3, characterized in that The providing of the second solvent includes: mixing the surfactant with the poor solvent to obtain the second solvent.

5. The method according to any one of claims 1 to 4, characterized in that: The mixing of the mixed liquid with the second solvent comprises: adding the mixed liquid into the continuously stirred second solvent at a certain flow rate and mixing until the first solvent and the poor solvent reach a preset volume ratio.

6. The method according to claim 5, characterized in that The preset volume ratio is determined based on the mutual solubility of the first solvent and the poor solvent.

7. The method according to claim 5, characterized in that The method satisfies at least one of the following characteristics: The flow rate of adding the second solvent to the mixed solution is 1 to 200 mL / min; The stirring speed of the second solvent is 50 to 500 rpm / min; The preset volume ratio between the first solvent and the poor solvent is 1:(3.3-50).

8. The method according to any one of claims 1 to 4, characterized in that: The method satisfies at least one of the following characteristics: The crude crystal product is washed 2 to 5 times; The drying process in step S4 includes: performing step-by-step heat treatment on the cleaned crude crystal product to obtain lithium indium halide nanocrystals.

9. The method according to claim 8, characterized in that The stepwise heat treatment includes a first heat treatment and a second heat treatment. The heat treatment temperature in the first heat treatment is 100-250° C. and the time is 3-5 hours. The heat treatment temperature in the second heat treatment is 350-450° C. and the time is 1-5 hours.

10. An all-solid-state battery, comprising a positive electrode layer, a negative electrode layer and a separator layer, characterized in that: At least one of the positive electrode layer and the isolation layer comprises lithium indium halide nanocrystals prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Modified Li3MX6 solid electrolyte material, preparation method, application and lithium metal solid-state battery thereof

    CN120127205A